2011
DOI: 10.1007/s12263-011-0252-8
|View full text |Cite
|
Sign up to set email alerts
|

Benfotiamine increases glucose oxidation and downregulates NADPH oxidase 4 expression in cultured human myotubes exposed to both normal and high glucose concentrations

Abstract: The aim of the present work was to study the effects of benfotiamine (S-benzoylthiamine O-monophosphate) on glucose and lipid metabolism and gene expression in differentiated human skeletal muscle cells (myotubes) incubated for 4 days under normal (5.5 mM glucose) and hyperglycemic (20 mM glucose) conditions. Myotubes established from lean, healthy volunteers were treated with benfotiamine for 4 days. Glucose and lipid metabolism were studied with labeled precursors. Gene expression was measured using real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
0
15
0
1
Order By: Relevance
“…We are unclear how precisely this occurs, but previous research work suggests that this may constitute an energy‐conserving mechanism (by promoting glucose oxidation) (Fraser et al . ) and/or a direct effect of BFT on neurohormonal modulation (Katare et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…We are unclear how precisely this occurs, but previous research work suggests that this may constitute an energy‐conserving mechanism (by promoting glucose oxidation) (Fraser et al . ) and/or a direct effect of BFT on neurohormonal modulation (Katare et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that cisplatin treatment decreases GSH levels . BFT increases the thiamine level that activates transketolase and downregulates NADPH oxidase; consequently, NADPH production is increased . This replenishes the cellular GSH; therefore, BFT protects the kidneys from the damaging effect of cisplatin .…”
Section: Discussionmentioning
confidence: 99%
“…Benfotiamine but not thiamine increased glucose oxidation while lipid oxidation and metabolism was influenced by neither of the two. Benfotiamine also down-regulated NADPH oxidase 4 expression [36] .…”
Section: Thiamine Mishandling In Diabetesmentioning
confidence: 94%